Evaluation of Water Quality Indexes and Heavy Metal Pollution Indexes of Different Industrial Effluents and Karnaphuli River Water in Chattogram, Bangladesh - Md. Didarul Alam, Chowdhury; Tabassum, Billah; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri; Sagor, Barua; A. J. M., Morshed; Ektiar, Uddin; Muhammad Misbah, Uddin (John Wiley & Sons, 2024)
The study evaluated the water quality index (WQI) and heavy metal pollution index (HPI) of different industrial effluent and surface water from various sites of the Karnaphuli River, based on collected from 20 different industries, including textile dyeing, textile washing, oil processing, chemicals, and tannery, and 17 stations of the Karnaphuli River, from the Kalurghat Bridge to the estuary where the river meets with the Bay of Bengal. This study was carried out in the dry season of the 2021–2022 fiscal year. Six physicochemical parameters, namely pH, biochemical oxygen demand, chemical oxygen demand, total dissolved solids, electrical conductivity, and hardness, were taken for the determination of the WQI, and concentration of heavy metals (Pb, Fe, Cd, Cu, Cr, Mn, and Ni) were considered for the calculation of the HPI. Both indexes were calculated against the Bangladesh Standard (denoted by subscript a) and WHO standards (denoted by subscript b). The water quality indexes WQIa and WQIb for industrial effluent ranged from 11.66 to 176.77 and 44.45 to 9703.99, respectively. Samples namely TD-5, TD-7, TD-8, TD-9, TD-10, OS-1, and C-1 showed excessively high WQI value. On the other hand, the HPIa and HPIb of industrial effluent varied from 43.6 to 167,785.3 and 0.34 to 18,412.3, respectively. Furthermore, oil processing and chemical effluents showed noticeably higher HPI values than other industrial samples. Both WQI and HPI values indicated a serious pollution load in most experimental samples. No river water sample showed a WQI value below 100, denoting it was unfit for consumption. The water quality indexes WQIa and WQIb for river water samples ranged from 1275.40 to 29,405.77 and 131.20 to 5860.99, respectively. According to the Bangladesh Standard, the river water samples were moderately to highly polluted by metal. The highest HPI value for the river water sample was 7965, denoting extreme metal pollution. The investigation revealed that most industrial effluents and Karnaphuli River water samples contained significant pollution load. Therefore, effective measures must be adopted immediately for future sustainability to cope with this contamination. The results emphasize the immediate requirement for strict regulations and advanced water treatment technologies to reduce contamination risks in the Karnaphuli River. Prompt action by authorities is essential to safeguard the river, prevent ongoing ecological damage, and address metal accumulation in fish affecting the food chain. Public awareness and legislative measures are vital for ecosystem preservation.